Economic Analysis Of Mungbean (Vigna Radiata) Cultivation In Some Coastal Areas Of Bangladesh - Islam, QM Shafiqul; Rahman, MS; Hossain, MA; Hossain, MS (Bangladesh Journal of Agricultural Research, 2011)
The study was conducted in two coastal mungbean growing districts, namely Noakhali and Patuakhali of Bangladesh during the period of 2008-09 with a view to estimating the technical efficiency of mungbean growers. The study revealed that mungbean production was found profitable. The benefit cost ratio (BCR) was 2.22 on full cost basis. The estimated results showed that the average level of technical efficiency among the sample farmers was 89%. This implies that given the existing technology and level of inputs, the output could be increased by 11 percent. Farmer’s education and experience had positive significant effect on mungbean production. Fifty nine percent farmers produced outputs to the maximum frontier output level. Farmers in the study area mentioned some constraints like high price of fertilizer, insecticides, severe attack of insects, etc. to the production of mungbean at farm level. Keywords: Profitability; mungbean; technical efficiency. DOI: http://dx.doi.org/10.3329/bjar.v36i1.9227 BJAR 2011; 36(1): 29-40